A camp of points and Troublesome: spatial and lithic perspectives on site structure and mobility at Porcupine Peak (5ST98), Colorado - Kuhr, Aleah G., author; LaBelle, Jason M., advisor; Van Buren, Mary, committee member; Payne, Sarah, committee member (Colorado State University. Libraries, 2025)
This thesis presents the results of an archaeological investigation at Porcupine Peak (5ST98), a prehistoric camp excavated in the late 1970s, situated in Summit County of the Colorado Rockies. Although excavated nearly 50 years ago, the site had never received an official report until now. This thesis presents the first detailed analysis of the site's artifact assemblage and spatial organization, drawing on newly compiled provenience data and lithic descriptions. Spatial analysis was used to examine artifact distribution and identify activity areas, while lithic attributes provide insights into reduction strategies and raw material use. These patterns are integrated into a study of site structure and land use, with particular attention to mobility strategies in the high-altitude environment of the Colorado Rockies. Typological analysis of projectile points indicates traces of occupations spanning ~12,000 BP to ~410 BP, with Late Archaic use (3,000–1,800 BP) dominating the record. This conclusion is supported by the high frequency of Late Archaic corner-notched dart points, radiocarbon dates, and the intensive use of Troublesome chert. ArcGIS Pro was used to conduct horizontal and vertical spatial analysis, revealing a dominance in Late Archaic activity within a high elevation environment and evidence for activity areas related to camp use. Analysis of Kremmling (Troublesome) chert shows that distance from the quarry shaped lithic use, with Porcupine Peak reflecting curated technological strategies and the careful management of non-local stone alongside expedient local materials. The results suggest that Porcupine Peak functioned as a temporary camp site, primarily used during the Late Archaic, where tool maintenance, cooking, and food processing took place. This study contributes to understanding hunter-gatherer mobility, site use, and high-altitude adaptations in the Colorado Rockies.
Keywords: lithics; Rocky Mountains; spatial; mobility; excavation; site structure